PENGARUH MOTIVASI, PELATIHAN KERJA DAN DISIPLIN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PT. BHUMI PHALA PERKASA BALIKPAPAN: PENGARUH MOTIVASI, PELATIHAN KERJA DAN DISIPLIN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PT. BHUMI PHALA PERKASA BALIKPAPAN - Reinata, Nella; Yusuf, Tamzil; Arrywibowo, Imam (MEDIA RISET EKONOMI [MR.EKO], 2024)
This research aims to determine the influence of motivation, work training and work discipline on employee morale at PT. Bhumi Phala Perkasa Balikpapan. The population in this study were 141 employees of PT. Bhumi Phala Perkasa Balikpapan. By using a purposive sampling technique, the sample used was 81 respondents. The data collection method was carried out by distributing questionnaires. This research uses SmartPLS to manage data. The results of this research indicate that the Motivation variable has a positive and significant effect on the Work Spirit of PT. Bhumi Phala Perkasa Balikpapan. The Job Training variable has a positive and significant effect on the Work Spirit of PT. Bhumi Phala Perkasa Balikpapan. The Work Discipline variable has a positive and significant effect on the Work Spirit of PT. Bhumi Phala Perkasa Balikpapan.